An insight into methanol oxidation mechanisms on RuO2(100) under an aqueous environment by DFT calculations. Issue 11 (6th March 2017) - Sheng, Tian; Ye, Jin-Yu; Lin, Wen-Feng; Sun, Shi-Gang
Abstract : In this work, we have studied methanol oxidation mechanisms on RuO2 (100) by using density functional theory (DFT) calculations and ab initio molecular dynamics (MD) simulations with some explicit interfacial water molecules. Abstract : In this work, we have studied methanol oxidation mechanisms on RuO2 (100) by using density functional theory (DFT) calculations and ab initio molecular dynamics (MD) simulations with some explicit interfacial water molecules. The overall mechanisms are identified as: CH3 OH* → CH3 O* → HCHO* → HCH(OH)2 * → HCHOOH* → HCOOH* → mono-HCOO* → CO2 *, without CO formation. This study provides a theoretical insight into C1 molecule oxidation mechanisms at atomic levels on metal oxide surfaces under an aqueous environment.